School principals’ instructional supervision strategies for enhancing teachers’ capacity for self-renewal - Sutarsih, Cicih; Saud, Udin S.; Herdiyanti, Kristi (Universitas Jambi, Indonesia, 2025)
Education demands continuous teaching and self-renewal to maintain instructional relevance amid evolving demands. This qualitative study examines the instructional supervision strategies employed by the principal at SD Pelita Fajar Elementary School to enhance teachers' capacity for self-renewal. Data were gathered through observation, interviews, and document analysis, and analyzed via NVivo 14 following Miles, Huberman, and Saldaña's interactive model. Findings indicate that the principal implements collaborative, evidence-based strategies across planning, implementation, follow-up, and evaluation phases, anchored in instructional leadership. These foster a structured self-renewal cycle—exploration (diverse knowledge sourcing), exploitation (innovative media creation), absorption (skill internalization), and integration (collaborative embedding)—while addressing barriers like time constraints and low motivation through targeted solutions. The approach significantly enhances teachers' adaptability, problem-solving skills, and professional growth, underscoring the crucial role of supervision in sustainable development.